Mobile-Assisted Mind Mapping (MAMMAT) as a Tool to Support University Students’ Argumentative Writing - Karim, Rafidah Abd; Mohd Adnan, Airil Haimi; Abu, Abdul Ghani; Idris, Noorzaina; Ismail, Izwah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study examined the use of a mobile-based technological tool known as Mobile-assisted Mind Mapping Technique (MAMMAT) to support ESL university students’ argumentative writing skills performance. The participants of this study were 45 ESL university students from two lecture groups at a public university campus in Peninsular Malaysia. The study employed a quasi-experimental research design. The experimental group was taught utilizing the MAMMAT whilst the control group was taught utilizing the conventional method. The pre-test and post-test scores were analysed through analysis of covariance (ANCOVA). The analysis of covariance (ANCOVA) results showed that there were statistically significant differences between the groups when test items were measured. As a conclusion, the MAMMAT has supported ESL university students’ argumentative writing skills performance. The study implicates that the use of MAMMAT can support students’ argumentative writing in ESL classroom.